1986
DOI: 10.1037/0003-066x.41.7.783
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of alcoholism reconsidered: The case for a biopsychosocial process.

Abstract: D. A. (2000). The clinical and social ecology of childhood for children of alcoholics: Description of a study and implications for a differentiated social policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
132
0
5

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(149 citation statements)
references
References 72 publications
12
132
0
5
Order By: Relevance
“…These findings are consistent with reports that subjects with alcoholism are more aggressive and impulsive, and have more suicidal ideation than controls or psychiatric subjects without a history of alcoholism (Nicholls et al, 1974;Hesselbrock et al, 1985;Zucker and Gomberg, 1986;Cloninger et al, 1988;Cornelius et al, 1995Cornelius et al, , 2001Bates and Labouvie, 1995;Caspi et al, 1997;Badawy, 1998;Pihl and LeMarquand, 1998;Sher et al, 1999). Prospective studies have demonstrated that impulsive individuals are at elevated risk for the development of alcohol-related problems (Bates and Labouvie, 1995;Caspi et al, 1997;Cloninger et al, 1988;Zucker and Gomberg, 1986;Sher et al, 1999). Aggressive and impulsive behaviors may be a manifestation of underlying personality pathology, or signs of a developmental disorder, or both, that contribute to the development of alcoholism (Sher et al, 1999).…”
Section: Clinical Featuressupporting
confidence: 82%
“…These findings are consistent with reports that subjects with alcoholism are more aggressive and impulsive, and have more suicidal ideation than controls or psychiatric subjects without a history of alcoholism (Nicholls et al, 1974;Hesselbrock et al, 1985;Zucker and Gomberg, 1986;Cloninger et al, 1988;Cornelius et al, 1995Cornelius et al, , 2001Bates and Labouvie, 1995;Caspi et al, 1997;Badawy, 1998;Pihl and LeMarquand, 1998;Sher et al, 1999). Prospective studies have demonstrated that impulsive individuals are at elevated risk for the development of alcohol-related problems (Bates and Labouvie, 1995;Caspi et al, 1997;Cloninger et al, 1988;Zucker and Gomberg, 1986;Sher et al, 1999). Aggressive and impulsive behaviors may be a manifestation of underlying personality pathology, or signs of a developmental disorder, or both, that contribute to the development of alcoholism (Sher et al, 1999).…”
Section: Clinical Featuressupporting
confidence: 82%
“…In particular, the BU components of impulsivity (as measured by the TPQ Novelty Seeking scale) and interpersonal exploitativeness (as measured by the reversed EPQ-R Lie scale) each accounted for unique genetic variation in AD risk. The results of the present study, considered in the context of the cumulative evidence from longitudinal studies linking earlier BU with later AD (Caspi et al, 1997;Cloninger et al, 1988;Loperet al, 1973;Zucker & Lisansky Gomberg, 1986) and studies of offspring of alcoholics identifying elevations in BU among individuals at risk for AD (e.g., Finn et al, 2000;Sher at al., 1991), provide further support for the theory that the genetic diathesis for AD is partially mediated by the personality dimension of BU tLIomnger, I9lS/a; Ianer, I9lSlS; Ianer et al, I~!S:); ÂŁUClcerman, 1987). Several mechanisms have been advanced to explain the causal link between genetically influenced variation in BU and future AD (Sher et al, 1999).…”
Section: Bu and Genetic Risk For Admentioning
confidence: 99%
“…First, genetic factors have been consistently implicated in contributing to individual differences in personality traits, with about one third to one half of the variation in personality typically being attributed to such factors (Eaves, Eysenck, & Martin, 1989;Loehlin, 1992). Second, cross-sectional studies consistently show associations of several personality traits with a history of alcoholism (McGue, Slutske, Taylor, & Iacono, 1997;Sher & Trull, 1994;Sher, Trull, Bartholow, & Vieth, 1999), and longitudinal studies provide evidence that at least some of these personality correlates are developmental antecedents of alcoholism (Caspi et al, 1997;Cloninger, Sigvardsson, & Bohman, 1988;Loper, Kammeier, & Hoffman, 1973;Zucker & Lisansky Gomberg, 1986). Specifically, the traits of impulsivity, thrill seeking, rebelliousness, nonconformity, and aggressiveness (i.e., "behavioral undercontrol"; Sher, 1991) are robust predictors of alcoholism.…”
mentioning
confidence: 99%
“…10 Diagnostic classifications distinguish between alcohol dependence (AD) and alcohol abuse. Under the current and widely used criteria from the American Psychiatric Association, 11 symptoms of AD include direct indices of physiological dependence (withdrawal, tolerance) as well as behavioral indices of addiction (lack of control over amount consumed, binge drinking, inability to quit drinking, continued use despite serious medical or psychiatric consequences, and drinking to the exclusion of other activities).…”
Section: Introductionmentioning
confidence: 99%